How the development of barren land into orchards affects soil ecosystem in Tibet, China - LI, Shuailin; WANG, Shuo; ZENG, Xiuli; CUI, Yongxing; YU, Wantai; MA, Qiang (Pedosphere, 2022)
Fruit production is an important strategy for alleviating poverty on the Tibetan Plateau and leads to the conversion of natural barren land into orchards. This study aimed to understand how the conversion of barren land to peach (Prunus persica) orchards affects soil nutrients, heavy metals, and fungal communities in the 0–40 cm profile (at 20 cm intervals) in an experiment including three treatments, barren land (BL), peach orchards planting for 4 years (Y4), and peach orchards planting for 10 years (Y10). Results of the experiment showed that compared with BL, Y4 reduced the availability of some macronutrients (N and K) and micronutrients (Fe and Mn) due to the exclusive application of chemical fertilizer at the seedling stage. Conversely, Y10, which included six years of green cultivation management, using a combination of sheep manure and chemical fertilizer as well as alfalfa (Medicago sativa Linn) intercropping, effectively improved soil macronutrients, but did not enhance the availability of Fe and Mn. Although the investigated heavy metals (As, Hg, Pb, Cr, and Cd) in both the Y4 and Y10 soils were found to pose a low risk to food safety and soil environment, Hg, Cr, and As tended to accumulate in the subsoil (20–40 cm). Furthermore, the variations in the fungal community composition and functional groups were mainly driven by the interaction effects of macronutrients, micronutrients, and heavy metals, but their independent contribution to specific key functional groups cannot be overlooked. For example, Y4 and Y10 decreased the relative abundance of soil saprotrophic and lichenized fungi, mainly due to the loss of micronutrients (Fe and Mn). However, as a result of macronutrient input and dung saprotrophic fungi enrichment, orchard soils promoted the growth of pathogens that play critical roles in fungal co-occurrence networks. These findings indicate that supplementation with N or K fertilizer or manure at the seedling stage and fertilizers rich in Fe and Mn throughout the growth period would be beneficial to the balance of soil nutrients and provide insights into linking the variations in soil nutrients and heavy metals to the function of the fungal community during the conversion of barren land to orchards in alpine soil ecosystems. The risks posed by heavy metal accumulation and fungal pathogen enrichment should be actively prevented.